A novel method: Nickel and cobalt extraction from citric acid leaching solution of nickel laterite ores using oxalate precipitation. (January 2023) - Astuti, Widi; Nurjaman, Fajar; Rofiek Mufakhir, Fika; Sumardi, Slamet; Avista, Dira; Cleary Wanta, Kevin; Tri Bayu Murti Petrus, Himawan
Highlight: Mixed oxalate precipitate (MOP) was produced from citric acid leaching of nickel laterite ores and direct oxalate precipitation. The purity of MOP is 78%. Leaching efficiency of nickel was around 90%; while efficiency of nickel oxalate precipitation was 100%. This method is an alternative for recovering nickel from nickel laterite ores that is simpler and ecofriendly. Abstract: In this study, an alternative method for recovering nickel and other valuable metals from nickel laterite ores is proposed and evaluated. The proposed method comprises a leaching step using citric acid to dissolve the nickel and cobalt from Indonesian nickel laterite ores, and subsequently, an oxalate precipitation step to precipitate the nickel (and cobalt) from citric acid leach filtrate. The results of the leaching experiments showed that nickel (and cobalt) can be dissolved in the leaching step using 1 M citric acid solution at 80 °C, a pulp density of 100 g/L, and leaching duration of 5 h. The results of the oxalate precipitation experiments showed that complete precipitation of nickel can be achieved at 80 °C, 500 rpm stirring speed, and precipitation duration of 3 h. This proposed method can produce Mixed Oxalate Precipitate (MOP) with a purity of 78 %.